Building up Students’ Reading Comprehension Through Strategy Using Authentic Materials at Senior High School - Nurul Jihad; Nasriandi Nasriandi; Jusriati Jusriati (Institut Agama Islam Negeri Palopo, 2023)
Building up Studentsâ€™ Reading Comprehension through Peer Review Strategy using Aunthentic Materials at SMP Negeri 10 Palopo. The objective of this research was to find out the effectiveness of Peer Review Strategy using Aunthentic Materials in teaching reading comprehension at SMP Negeri 10 Palopo. The researcher applied pre-experimental design. The population of this research was the eighth grade students of SMP Negeri 10 Palopo. The total number of population was 247 students. In determining the sample, the researcher used cluster random sampling technique and the researcher took 24 students as sample. The instrument of this research were reading test. The result of the research shows that the use of Peer Review strategy using Authentic materials is effective in teching reading comprehension. It is proven that the mean score of the pre-test is 53.08 and the mean score of the post-test is 70.96. The standard deviation of pre-test is 16.795 and the standard deviation of post-test is 15.730. While t-test = 0,000, (Î±) = 0.05. It means that t-test is smaller than (Î±), so there is a significant different between pre-test and post-test of students reading comprehension before and after the researcher gave the treatment. It is showed that the null hypothesis (Ho) is rejected, while the alternative hypothesis (H1) is accepted. Therefore, it can be conculded that Peer Review Starategy in Authentic Materials is effective in teaching reading comprehension.Â